Inherent Load Measurement and Component Identification by multi-dimensional Coded Data in the Component's Subsurface Region. (2016) - Barton, Sebastian; Mroz, Gregor; Reimche, Wilfried; Maier, Hans Jürgen
Abstract: In industrial production, the absence of component markings and unrecognized component failure can result in a lack of protection against product piracy and malfunctions of machinery and installations. A technique for storing data inherently in the subsurface region of the component was developed. Inherently stored data is highly resistant to external stresses and inseparably linked to the component. To evaluate the integrity of highly stressed components, material inherent sensors are induced in the subsurface region of the component to store the loading history. These techniques offer the potential for securely identifying and evaluating the status of components, and thus reducing failure costs.